Natural sciences and social sciences learning in school garden, Indonesian School of the Haque, Netherlands - S. Syamsia; Herman Tahir; Ilman Abdurofi; R. Rahmi; Asriyanti Syarif (Universitas Muhammadiyah Malang, 2023)
School gardens can be used as a source of student learning for various subjects in an integrated manner to improve student’ academic, personal, awareness, and social abilities. By implementing gardening activities students are trained to design, build and develop agricultural hustles at school through cultivating and harvesting the plants that may be consumed and added economic value. The service activity aims to utilize the school garden as a medium for learning natural science and social Science at the Indonesian school of the Hague. Methods of implementing activities consist of preparing materials tools, preparing seeds, clearing land, planting, caring for plants, observing the students’ behavior toward school gardens, and evaluating students’ understanding of school subject matter based on learning resources in the school garden. Based on students’ responses in answering questions related to science material and social science impacts, it shows that both science and social science learning activities in school gardens may assist in an in-depth understanding of the concept of agriculture skills and behaviors of the students.